1994
DOI: 10.1111/j.1440-0960.1994.tb01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Adams‐oliver Syndrome: Aplasia Cutis Congenita, Terminal Transverse Limb Defects and Cutis Marmorata Telangiectatica Congenita

Abstract: A male infant with the features of Adams-Oliver syndrome is described. These features included severe aplasia cutis congenita (ACC) of the scalp involving both skin and cranium, a shortened right foot with talipes equinovarus, extensive cutis marmorata telangiectatica congenita and also haemangiomas and ulceration of the abdominal skin. Exposure of the dural membrane was associated with infection, hyponatraemia and finally localised necrosis with herniation of brain and fatal cerebral haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 10 publications
1
25
0
3
Order By: Relevance
“…Scalp ACC may be accompanied with underlying bony defect leading to serious complications such as encephalocoele, meningitis, and hemorrhage. [3] Probands The presence of two major is sufficient for diagnosis while the combination of one major and one minor is denoted a high likelihood of AOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scalp ACC may be accompanied with underlying bony defect leading to serious complications such as encephalocoele, meningitis, and hemorrhage. [3] Probands The presence of two major is sufficient for diagnosis while the combination of one major and one minor is denoted a high likelihood of AOS.…”
Section: Discussionmentioning
confidence: 99%
“…The first report of AOS was described as an autosomal dominant disorder by Adam and Oliver, however, further case reports suggested that its occurrence is more commonly sporadic. [1], [3] Synonymaplasia cutis congenita with terminal transverse limb defects Case Report A full term, appropriate for gestational age baby, was born to G3P2L2 mother by normal vaginal delivery with multiple congenital anomalies in the form of aplasia cutis (Fig.1) over the scalp with limb anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Eskar dokusunun kurutlanıp ayrılma-sı veya cerrahi işlemler sırasında ölümle sonuçla-nabilecek kanamalar meydana gelebilmektedir (7,8). Açık defektten BOS sızıntısı ile gelişen elektrolit denge bozukluğu bebeğin genel durumunu kö-tüleştirebilmektedir.…”
Section: ö öZ Ze Et Tunclassified
“…Defektin altındaki açık doku enfeksiyon riskini arttırmaktadır. Fatal menenjit ve ensefalit gelişebilir (8). Defektin erken süreçte cerrahi olarak kapatılması tanımlanan komplikasyonların önlenmesi ve daha iyi kozmetik sonuçların elde edilmesi açısından önerilmektedir.…”
Section: ö öZ Ze Et Tunclassified
“…AOS is a rare congenital disorder including congenital scalp and skull defects, extremity anomalies, occasional mental retardation, and congenital heart disease (2)(3)(4)(5) . The association of cutis marmorata telengiectatica congenita with this syndrome has been described (3,4,6) . The expression of scalp defects sometimes includes bone deformities, and limb defects can vary from nail dystrophy to complete absence of distal extremities.…”
Section: Introductionmentioning
confidence: 99%